Isolation and identification of biocellulose-producing bacterial strains from Malaysian acidic fruits - Voon, Wendy Wen Yi; Rukayadi, Yaya; Meor Hussin, Anis Shobirin (The Society for Applied Microbiology, 2016)
Biocellulose (BC) is pure extracellular cellulose produced by several species of micro-organisms that has numerous applications in the food, biomedical and paper industries. However, the existing biocellulose-producing bacterial strain with high yield was limited. The aim of this study was to isolate and identify the potential biocellulose-producing bacterial isolates from Malaysian acidic fruits. One hundred and ninety-three bacterial isolates were obtained from 19 local acidic fruits collected in Malaysia and screened for their ability to produce BC. A total of 15 potential bacterial isolates were then cultured in standard Hestrin-Schramm (HS) medium statically at 30°C for 2 weeks to determine the BC production. The most potent bacterial isolates were identified using 16S rRNA gene sequence analysis, morphological and biochemical characteristics. Three new and potent biocellulose-producing bacterial strains were isolated from soursop fruit and identified as Stenotrophomonas maltophilia WAUPM42, Pantoea vagans WAUPM45 and Beijerinckia fluminensis WAUPM53. Stenotrophomonas maltophilia WAUPM42 was the most potent biocellulose-producing bacterial strain that produced the highest amount of BC 0·58 g l−1 in standard HS medium. Whereas, the isolates P. vagans WAUPM45 and B. fluminensis WAUPM53 showed 0·50 and 0·52 g l−1 of BC production, respectively.